Four-Wave-Mixing in Zirconia-Yttria-Aluminum Erbium Codoped Silica Fiber - Ahmad, Harith; Paul, Mukul Chandra; Awang, Noor Azura; Harun, Sulaiman Wadi; Pal, Mrinmay; Thambiratnam, Kavintheran (European Optical Society, 2012)
The generation and characterization of the Four-Wave-Mixing (FWM) effect in an Erbium Doped Zirconia-Yttria-Alumino Silicate Fiber (EDZF) is described. The EZDF is fabricated from a conventional silica preform by Modified Chemical Vapour Deposition (MCVD) and also solution doping to add glass modifiers and nucleating agents, with the resulting preform annealed and drawn into a fiber strand with a 125 ± 0.5 μm diameter. A 4 m long EZDF, ZEr-B with a propagation loss of 0.68 dB/m and an erbium concentration of 3000 ppm is used to investigate the FWM effect. The FWM power levels are measured to be approximately - 45 dBm at a region of 1565 nm and show good agreement with the theoretical predicted values. A non-linear coefficient of 14 W-1km-1 is also measured, along with chromatic and slope dispersion values of 28.45 ps/nm.km and 3.63 ps/nm2.km, which agree with the predicted values. The fabricated ZEr-B fibre has many potential applications utilizing the FWM effect, including the generation of multi-wavelength outputs.